Use of the peanut ball during labour: A systematic review and meta‐analysis - Parivash Ahmadpour; Sakineh Mohammad‐Alizadeh‐Charandabi; Rana Doosti; Mojgan Mirghafourvand (Wiley, 2021)
Abstract Aim This study aimed to determine effectiveness of peanut ball on the duration of the stages of labour and frequency of caesarean section. Design A systematic review and meta‐analysis. Method A comprehensive electronic search was carried out with no time limit until December 2020. Collected data were analysed using software RevMan‐ version 5.3. Heterogeneity was assessed using I2, T2, and 2. GRADE approach was used to assess the certainty of evidence. Results The meta‐analysis on six clinical trials with 645 participants showed no statistically significant difference between the two groups in caesarean surgery rate (RR = 0.82) and length of the first (MD = −15.64). Conclusions Therefore, further clinical trials with stronger evidence should be carried out to assess the effectiveness of peanut ball on caesarean surgery rate and length of first and second stages of labour.